Cabbage whiteflies colonise Brassica vegetables primarily from distant, upwind source habitats. Issue 8 (22nd August 2019) - Ludwig, Martin; Ludwig, Hella; Conrad, Christopher; Dahms, Thorsten; Meyhöfer, Rainer
Abstract: The occurrence of species in rapidly changing environments, such as agricultural landscapes, is affected by their ability to recolonise habitats. Knowledge of the landscape scale affecting colonisation is essential for large‐scale pest management. Colonisation by insects can be affected on multiple landscape scales, as different morphs of a species may have specific dispersal abilities. The cabbage whitefly, Aleyrodes proletella (L.) (Hemiptera: Aleyrodidae), a major pest of Brassica vegetables, is known to colonise Brassica vegetables primarily from fields of oilseed rape, Brassica napus L. (Brassicaceae). We used field mapping and remote sensing to characterise the relevant scales for colonisation of Brussels sprouts by cabbage whiteflies. Surprisingly, oilseed rape fields in wide landscapes (2–8 km around study sites) explained colonisation better than oilseed rape areas in local landscapes (200–1 000 m around study sites). The explained variance increased when additional weight was given to upwind source habitats, indicating wind transport of whitefly colonisers. Low importance of local compared to wide landscape source habitats can be explained by the flight behaviour of whitefly morphs. Migratory morphs show phototactic attraction but are attracted by hosts only during the later phases of flight. Therefore, they ignore host plants close to their origin and disperse several kilometres. Trivial flight morphs rarely move more than a few hundred metres. In conclusion, as most whitefly colonisers reached Brassica vegetables from source habitats at a distance of 2–8 km, predictions on pest pressure and landscape‐scale whitefly management should consider these distances. In contrast, oilseed rape fields in the local landscape, which usually worry farmers, had little effect. Abstract : The study investigates the spatial scale relevant for colonisation of Brussel sprouts by cabbage whiteflies, Aleyrodes proletella (Hemiptera: Aleyrodidae). Source habitats in landscape radii >2 km were more important than source habitats in smaller radii. This can be explained by the specific flight behaviour of two whitefly morphs. Importance of upwind source habitats indicated wind dispersal. Predictions of whitefly pest pressure and landscape‐scale whitefly management should consider source habitats at distances >2 km.